The effect of good corporate governance on financial performance in the financial sector - Putri Sekarini Hendrawan; Fadhia Pramesti; Friscilla H M Budiman; Victoria R M Wattimena; Lila Meilinda (Privietlab, 2022)
This study examines the effect of Good Corporate Governance (GCG) on the financial performance of Islamic banks in Indonesia, with a focus on the period 2011–2014. Financial performance, measured by Return on Assets (ROA), serves as the dependent variable, while GCG components such as the board of directors, independent commissioners, sharia supervisory board, and audit committee act as independent variables. Using panel data regression analysis through Eviews 9.0, the results reveal that only the board of directors significantly and positively impacts financial performance (t = 3.123652, p < 0.05). Conversely, independent commissioners, the sharia supervisory board, and the audit committee demonstrate no significant effect on ROA. The study highlights challenges such as concurrent positions held by supervisory boards and audit committees, leading to inefficiencies in governance. These findings underscore the pivotal role of the board of directors in enhancing financial performance within the context of Islamic banking, while other governance structures require reevaluation to optimize their contributions. This research contributes to the growing body of literature on GCG in the financial sector and offers practical insights for policymakers and practitioners in Islamic banking.